ILLOCUTIONARY ACTS REALIZED IN ANGELINA JOLIE’ SPEECH “EQUALITY FOR WOMEN” - Indah Nofitasari; Dyah Nugrahani; Entika Fani Prastikawati (Bajang Institute, 2023)
The purpose of this research is to find out what kind of illocutionary act that found in Angelina Jolie’s speech video and what is the frequent type of illocutionary act that used by Angelina Jolie on her speech “Equality for Women”. Descriptive qualitative method was used to investigate and describe Illocutionary Act of Angelina Jolie’s Speech: Equality for Women. The data of this study collected by analyzing the data from the video of Angelina Jolie’s speech entitled “Equality for Women”. From this study the researchers found that there are several kind of illocutionary act that used by Angelina Jolie on her speech such as declarative (3,1%), commissive (14%), directive (9,3%), expressive (18,7%), and representative (54,6%). The most frequent type of illocutionary act that Angelina Jolie used is representative with 35 data (54,6%). From the finding, it can be seen that the most frequent of illocutionary act found in Angelina Jolie speech video “Equality for Woman” was representative type. Angelina as a UN Defense emphasized reports and real facts abot issues and case of gender equality that was happenned around the world. By delivering this speech, Angelina Jolie provided a real overview about gender equality cases and issues. In line with the issues stated by Angelina, she expects that people will be more aware of gender equality and what they can do as a form of their contribution in helping realise the goals of the UN and people can better understand their rights in the future.